2010
DOI: 10.5222/terh.2010.43760
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent of Contrast Media Applications in Radiology: Assesment of Comprehensibility and The Anxiety Of The Patients

Abstract: ÖZET AMAÇ:Hastanemizde kullanılan onam formuna ait yazılı metnin okunabilirliğini, içeriğinin anlaşılabilirliğini saptamak ve kontrast madde onam formunun hastalarda uyandırdığı kaygıyı ve hastaların bilgilendirilmeye tepkilerini değerlendirmek. GEREÇ VE YÖNTEM:Çalışmaya Radyoloji Bölümü'ne kontrastlı Bilgisayarlı Tomografi tetkiki için başvuran 122 hasta alındı. Hastalardaki anksiyete şiddetinin bilgilendirme ile değişimini ölçmek için onam formu okutulmadan önce ve okutulduktan sonra beşli Görsel Analog Ölçe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…In some studies, it was found that being informed about the risks of treatment increased anxiety level in patients. 33 However, informing the patients about risks decreased the anxiety level according to other studies. 18,34,35 In our study, the participants who did not want to know the risks explained the reason for not wanting to know as "not being psychologically affected".…”
Section: Discussionmentioning
confidence: 88%
“…In some studies, it was found that being informed about the risks of treatment increased anxiety level in patients. 33 However, informing the patients about risks decreased the anxiety level according to other studies. 18,34,35 In our study, the participants who did not want to know the risks explained the reason for not wanting to know as "not being psychologically affected".…”
Section: Discussionmentioning
confidence: 88%
“…The Regulation also outlines the requisite content of information in consent forms, thereby lending support to the ethical and legal standards of the Turkish Medical Association's Code of Medical Ethics (hereinafter referred to as the Code) (8). Over the last few decades in Turkey, although studies have been conducted on how health care professionals obtain or should obtain informed consent (2,(9)(10)(11)(12)(13)(14)(15), there have been few studies on the content, readability, or conformity of the consent forms to ethical guidelines (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Cerrahi ve girişimsel işlemler, kan ve kan bileşeni kullanımı, sedasyon ve anestezi altında yapılan işlemler ile radyolojik tetkikler hasta onamı alınması gereken işlemlerden yalnızca birkaçıdır. 2,3 İletişim ve bilgi teknolojisi alanındaki gelişmelere paralel olarak, internet kullanımı yaygınlaşmış, lokal ve global iletişim biçimi değişmiştir. Türkiye İstatistik Kurumu Hane Halkı Bilişim Teknolojileri Kullanım Araştırması verilerine göre 16-74 yaş grubundaki bireylerde internet kullanım oranı 2012 yılına göre %79 oranında artış göstererek 2022 yılında %85 olarak açıklanmıştır.…”
unclassified